Algorithm-guided goal-directed haemodynamic therapy does not improve renal function after major abdominal surgery compared to good standard clinical care: a prospective randomised trial. Issue 1 (December 2016) - Schmid, Sebastian; Kapfer, Barbara; Heim, Markus; Bogdanski, Ralph; Anetsberger, Aida; Blobner, Manfred; Jungwirth, Bettina
Abstract Background Acute kidney injury is a common complication after major surgery. In this study, we investigated whether an algorithm-guided goal-directed haemodynamic therapy (GDT) can improve renal outcome compared to good standard clinical care. Methods A total of 180 patients undergoing major abdominal surgery were prospectively and randomly assigned to one of two groups: in the GDT group, patients were treated with a GDT algorithm using transpulmonary thermodilution while standard care was applied to the control patients. Change in creatinine was studied as the primary end point, postoperative complications as well as 1-year mortality as secondary outcomes. Haemodynamics in GDT and control patients were compared calculating goal-achievement rates. Results Postoperative change in creatinine (18 ± 39 μmol/l (control) vs. 16 ± 42 μmol/l (GDT); mean difference (95 % confidence interval) 1.6 μmol/l (−10 to 13 μmol/l)) was comparable between the GDT and the control group. Postoperative complications and mortality during hospital stay and after 1 year were not influenced by the use of a GDT algorithm. Achievement rates of haemodynamic goals were not higher in the GDT group compared to the already high (>80 %) rates in the control group. Multivariate regression analysis revealed intraoperative hypotension (MAP < 70 mmHg) and postoperative hypovolaemia (GEDI < 640 ml/m2 ) as risk factors for postoperative renal impairment. Conclusions In this study, GDT was not superior to standard clinical care in order to avoid renal failure after major abdominal surgery. The reason for this finding is most likely the high achievement rate of haemodynamic goals in the control group, which cannot be improved by the GDT algorithm. Trial registration Clinicaltrials.gov;NCT01035541 ; registered 17 December 2009.